Composition of R and D Expenditures: Relationship to Size of Firm, Concentration, and Innovative Output - Mansfield, Edwin (The Review of Economics and Statistics, 1981)
Edwin Mansfield, Composition of R and D Expenditures: Relationship to Size of Firm, Concentration, and Innovative Output, The Review of Economics and Statistics, Vol. 63, No. 4 (Nov., 1981), pp. 610-615